Incidence of velopharyngeal insufficiency and oronasal fistulae after cleft palate repair: A retrospective study of children referred to Isfahan Cleft Care Team between 2005 and 2009. Issue 10 (October 2015) - Hosseinabad, Hedieh Hashemi; Derakhshandeh, Fatemeh; Mostaajeran, Fatemeh; Abdali, Hossein; Davari, Heydar Ali; Hassanzadeh, Akbar; Kummer, Ann W.
Abstract: Objective: The purpose of this study is to determine the incidence of velopharyngeal insufficiency (VPI) and fistulae development in patients seen by the Isfahan Cleft Care Team and also determine the association of gender, age at repair, and cleft type with the incidence of each. Methods: This retrospective study was completed using records of patients referred to Isfahan Cleft Care Team between 2005 and 2009. One hundred thirty-one patients with a history of cleft palate (with or without cleft lip) who had undergone primary palate repair and were at least 4 years of age at the time of the speech evaluation were included in this review. The main outcome of this study was the incidence of fistulae and hypernasality following palatoplasty. A secondary outcome was the association of gender, age at the time of repair, and cleft type on the incidence of fistulae and hypernasality. Results: A post-surgical fistula was present in 23.7% of the patients studied. Fistula rates were significantly higher in patients who had undergone repair of bilateral clefts of the lip and palate (40.9%) than for those patients who had undergone repair of a unilateral cleft lip and palate (16.9%) ( p  = 0.02). Presence of a fistula was not associated with gender ( p  = 0.99) or age at time of primary surgical repair ( p  = 0.71). Mild hypernasality was noted in 15.3% of patients. Moderate or severe hypernasality was present in 66.5% of the patients and the remaining cases presented with normal resonance. Severe hypernasality was significantly higher in patients with a Veau IV type cleft as compared to patients with Veau III cleft types ( p  = 0.04). There was a significantly higher incidence of hypernasality in boys than in girls ( p  < 0.001). The association of age at the time of palatal repair and incidence of hypernasality was not significant ( r  = 0.13, p  = 0.07). Conclusions: Overall, post-surgical complications were high in this cohort of patients who had undergone cleft palate repair by Isfahan Cleft Care Team during the study time frame. Therefore, there is a high priority need for increased training of best practices for the surgeons.